Use of Rubber Process Analyzer for Characterizing the Molecular Weight Parameters of Natural Rubber - Tianming Gao; Ruihong Xie; Linghong Zhang; Hongxing Gui; Maofang Huang (International Journal of Polymer Science)
The aim of this work is to introduce a simple and rapid method for characterizing the molecular weight parameters and other molecular structure parameters of natural rubber (NR) using a rubber process analyzer (RPA). In this work, NR of different molecular weights was prepared by milling. Molecular weight parameters were measured by gel permeation chromatography coupled with laser light scattering (GPC-LLS) for comparison with RPA results. It was verified that increasing of milling time leads to a decrease of the number-average molecular weight (M-n), weight-average molecular weight (M-w), and molecular weight distribution (MWD). The dynamic and rheological properties were evaluated on RPA by tests of strain sweep, frequency sweep, and stress relaxation. These results were used to characterize the average molecular weight, MWD, and viscosity of NR and were found to agree with those from GPC-LLS. This convenient and rapid technology for characterizing NR molecular weight parameters would be especially useful in the elastomer industry.